A Multi-Criteria Decision Support System For Open Pit Mine Planning Under Geological And Market Uncertainties - Preprint 09-008 - S. A. Abdel Sabour (Society for Mining, Metallurgy & Exploration, 2009)
Conventional methods for selecting a production plan for an open pit mine is based on the assumption that ore grades throughout mine life as well as market variables are known with certainty. Another important issue that is also being ignored in the conventional procedure is the value of management flexibility to revise operating policy with time according to the arrival of new information. Based on this oversimplification of reality, an optimum mine plan that is thought to be maximizing net present value (NPV) of the project is selected. Given the multiple sources of risk affecting the estimated NPV, there is a high probability that the actual value will be different from that estimated. This could mislead decision making process regarding selecting an optimum mine plan. This paper proposes a multi-criteria ranking system for selection between alternative mine designs under both geological and market uncertainties. The system is based on integrating multiple market and geological uncertainties as well as the operating flexibility to revise the ultimate pit limits using a Monte Carlo-based real options valuation (ROV) model. To compare the methods, the article applies the proposed system, along with the conventional NPV-based method, to rank possible mine designs for a copper and a gold mine. It has been found that, considering multiple risk analysis measures while integrating uncertainty and operating flexibility results in selecting a mine design that is different from that selected by the conventional method.